أثر هيكل الملكية وخصائص أعضاء مجلس الادارة في جودة الأرباح دراسة تحليلية لعينة من الشركات الصناعية المدرجة في سوق العراق للأوراق المالية للمدة 2018 - 2021 - MOHAMMAD, SHIVAN AHMED; KAMAL , RONAK NASERADEEN (Journal of Duhok University, 2023)
This study aims to investigate the impact of each of the ownership structure and the characteristics of the members of the board of directors on the earnings quality of the of a sample of industrial companies listed in the Iraq Stock Exchange for the period 2018-2021. The study population represents the industrial companies listed in the Iraq Stock Exchange, while a sample was selected represented by a number of listed industrial companies depending on their market value and the daily trading volume of their shares in the market and according to the availability of the required data to extract indicators and measures of variables. In designing the structure of the study, it relied on the research onion adopted in recent studies in the faculties of management and economics in the world, according to which six levels of scientific methodology are determined, starting with the positive philosophy, the deductive approach, the strategy of the archival data approach, the quantitative method option, the use of longitudinal data and the reliance on secondary data from The annual reports and bulletins published on the Iraq Stock Exchange website, the Iraqi Securities Commission, and the websites of the study sample companies.The ownership structure measured by (the percentage of major shareholders and the percentage of foreign ownership) and the characteristics of the members of the board of directors measured by (the size of the board of directors, the diversity of the gender of the members of the board of directors, and the separation between the role of the managing director and the role of the chairman of the board of directors) were chosen as independent variables for their prominent role in influencing financial and non-financial decisions. In industrial companies and also for its important role in the corporate governance guide, while the dependent variable, which represents the necessary need for conducting this study, is the quality of profits, measured by (the appropriateness of value, and the accrual ratio).The multiple regression model was used to reach a set of conclusions, including that there is no relationship between the indicators of governance in the Iraqi industrial companies, the study sample, and the quality of profits as measured by the appropriateness of value. In general, and in the Iraq Stock Exchange in particular, and issuing a guide to corporate governance in this sector.